The Eurozone Crisis: Swimming naked in shark-infested waters - Bond, James (Sens public)

(untitled) (Département des littératures de langue française, 2011)
As the G20 leaders prepare to meet in Cannes to try to find a solution to the complex Eurozone crisis, which could unleash a global financial storm if no major initiative is taken, James Bond dives into the ramifications and the intricacies of a problem that now threatens the very existence of the European Union.